Fine-tuning signal strength in CD5 CAR-NK cells for targeted T cell cancer therapy - Jo, Seona; Lee, Yu Bin; Kim, Seok Min; Lee, Soo Yun; Choi, Myeongjin; Kyun, Mi-lang; Jeong, Seo Yule; Lee, Sunyoung; Kim, Ji Hyun; Kim, Yoonji; Kim, Yu Jung; Park, Sora; et al. (Frontiers in Immunology, 2025)
IntroductionT cell hematological malignancies are aggressive blood cancers that remain challenging despite various treatments. Current chimeric antigen receptor (CAR)-T and natural killer (NK) therapies show potential but struggle with nonselective elimination during tumor targeting. Since CAR signal strength is determined by the single-chain variable fragment (scFv) and CAR expression levels, fine-tuning these parameters enables selective recognition of malignant cells while preserving normal cells. Here, we aimed to develop optimized CD5 CAR-NK cells (OptiCAR-NK) to achieve potent anti-tumor activity with minimized off-tumor toxicity.MethodsWe engineered CD5 CAR-NK cells with different scFv and CAR expression levels. CAR expression was modulated by single-cell isolation and mRNA transfection to assess activity against both malignant and normal T cells in vitro. Therapeutic efficacy and safety were further validated in xenograft and humanized mouse models.ResultsOptimization of scFv and CAR expression levels (OptiCAR-NK) enabled selective recognition of CD5+ malignant T cells while maintaining strong anti-tumor activity with minimal toxicity. Mechanistic analysis revealed that NK cells’ innate ability to discriminate malignant from normal T cells depends on fine-tuned CAR signal strength and endogenous ligands on target cells.DiscussionOptimized modulation of scFv and CAR expression is crucial for designing a CAR that achieves high anti-cancer efficacy and is safe in normal cells. Our results suggest a promising avenue for optimized CD5 CAR-NK cell therapy to manage T cell malignancies while minimizing off-tumor effects.